2022
DOI: 10.1111/jbg.12741
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between inbreeding and milk production traits in two Italian dairy sheep breeds

Abstract: The effects of inbreeding in livestock species breeds have been well documented and they have a negative impact on profitability. The objective of this study was to evaluate the levels of inbreeding in Sarda (SAR, n = 785) and Valle del Belice (VdB, n = 473) dairy sheep breeds and their impact on milk production traits.Two inbreeding coefficients (F) were estimated: using pedigree (F PED ), or runs of homozygosity (ROH; F ROH ) at different minimum ROH lengths and different ROH classes. After the quality contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…The average value of the inbreeding coefficient in our study is 3.64%, which is within the range of average values compared to other populations. Although this coefficient is much higher than for extensively bred breeds (Kiya et al, 2019), it also reaches much lower values than for intensively bred breeds (Cesarani et al, 2023). It is true that the above-mentioned values of the inbreeding coefficient result in great variability between populations, which is also due to different mating management and different ways of using studs in herds.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The average value of the inbreeding coefficient in our study is 3.64%, which is within the range of average values compared to other populations. Although this coefficient is much higher than for extensively bred breeds (Kiya et al, 2019), it also reaches much lower values than for intensively bred breeds (Cesarani et al, 2023). It is true that the above-mentioned values of the inbreeding coefficient result in great variability between populations, which is also due to different mating management and different ways of using studs in herds.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, for the Morada Nova breed, the authors report an average value of 2.88 % (Matos and Lôbo, 2021). Another study on two breeds in Italy found a large variation in the inbreeding coefficient in different sheep populations, with one breed having an inbreeding value of 5.3 % and the other having an inbreeding value of 15.3 % (Cesarani et al, 2023). An inbreeding analysis of three meat breeds in Denmark showed variability in the inbreeding coefficient ranging from 1.2 % to 2.6 %, with an intergenerational increase in inbreeding of around 1 % (Norberg and Sorensen, 2007).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation